INDONESIAN UNIVERSITY STUDENTS’ VISUAL LEARNING STYLE: LEARNERS’ AND TEACHERS’ PERSPECTIVES - Maximeliana Masela; Adaninggar Septi Subekti (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aimed to investigate Indonesian undergraduate non-English department students' visual learning style and their and teachers' perspectives on the uses of visual aids to promote learning. It was conducted to fill the gap in the literature on the scarcity of empirical studies in the field of learning style in the Indonesian context despite the potentials of instruction accommodating learners' learning styles. 127 students participated in the study through a survey and descriptive analysis, this study found that the participants, in general, had a high level of visual learning style, suggesting that class instruction should provide visual media and activities reported to be effective by the participants. Four participants with the highest visual learning style levels along with three teachers of General English classes were interviewed. Through Thematic Analysis of the interview results, the study found that both the students and teachers reported that teachers used certain visual media for certain purposes, for example, pictures for brainstorming activities, videos for providing input for further discussions, and writing on the boards to explain grammar. Based on the findings, possible implications and contributions are mentioned along with limitations and possible future studies.